Emerging Social Burdens on Married Working Women in the Health Sector During Covid – 19 Pandemic - Kazan, Abdullah; Al-Saqr, Rawan Awad (Jordan Journal of Social Sciences, 2023)
The study aims to identify the social burdens that face Jordanian married women working in the health sector during Covid-19 Pandemic and to identify the statistical differences and their implications. To achieve the objectives of the study, the two methods of social survey and questionnaire are used as data collection tools. The study population consists of (237) women working in the health sector in Irbid Governorate who were selected by the convenience sampling method. The results of the study show that the percentages of the family burdens that faced married women during Covid-19 pandemic are high, whereas the percentages of the professional burdens are medium. The results also show that there are statistically significant differences at the level of significance (α = 0.05) among the averages of household burdens based on the variables of age, educational level, place of residence, number of family members, type of housing, and night shifts. The study also shows that there are no statistically significant differences at the level of significance α = 0.05 among the averages of occupational burdens based on the variables of educational level, number of family members, and type of housing.